Geo-Risk 2023 : Innovation in Data and Analysis Methods. - Ching, Jianye (Geotechnical Special Publications, 2023)
GSP 345 contains 46 peer-reviewed papers on innovation in data and analysis methods in geotechnical engineering presented at Geo-Risk 2023, held in Arlington, Virginia, July 23-26, 2023.